Effect of temperature change on the performance of the hybrid linear flow channel reactor and its implications on sulphate-reducing and sulphide-oxidising microbial community dynamics - Marais, T. S.; Huddy, R. J.; Van Hille, R. P.; Harrison, S. T. L. (Frontiers in Bioengineering and Biotechnology, 2022)
Semi-passive bioremediation is a promising strategy to mitigate persistent low volume mine-impacted wastewater containing high sulphate concentrations. Building on the proof of concept demonstration of the hybrid linear flow channel reactor (LFCR), capable of simultaneous biological sulphate reduction and partial sulphide oxidation with elemental sulphur recovery, the impact of key operating parameters, such as temperature, on process performance is critical to real-world application. Temperature fluctuates seasonally and across the diurnal cycle, impacting biological sulphate reduction (BSR) and partial sulphide oxidation. The process is reliant on the metabolic activity and synergistic interactions between sulphate-reducing (SRB) and sulphide-oxidising (SOB) microbial communities that develop within discrete oxic and anoxic microenvironments within the hybrid LFCR. In this study, the impact of operating temperature on process performance was evaluated by decreasing temperature with time from 30 to 10°C in each of three laboratory-scaled hybrid LFCR units operating in pseudo-steady state at 1 g/L sulphate. Using lactate as a carbon source, two reactor sizes (2 and 8 L) were considered, while the impact of lactate vs. acetate as carbon source was evaluated in the 2 L reactors. On incremental decrease in temperature from 30 to 10°C, a decrease in volumetric sulphate reduction rate was observed: from 0.144 to 0.059 mmol/L.h in the 2 L lactate-fed reactor; from 0.128 to 0.042 mmol/L.h in the 8 L lactate-fed reactor; and from 0.127 to 0.010 mmol/L.h in the 2 L acetate-fed reactor. Similarly, sulphate conversion efficiency decreased (2 L lactate-fed: 66% to 27%; 8 L lactate-fed: 61% to 20%; 2 L acetate-fed: 61% to 5%). A decrease in temperature below the critical value (15°C) led to considerable loss in metabolic activity and overall BSR performance. Sessile and planktonic microbial communities were represented by bacterial phyla including Proteobacteria, Synergistetes, Bacteroidetes, and Firmicutes. A diverse group of putative SRB (Deltaproteobacteria) and SOB, including Alpha, Beta, Gamma, and Epsilonproteobacteria phylotypes, were prevalent and shifted in relative abundance and community composition in response to decreasing temperature. Specifically, the decrease in the relative abundance of Deltaproteobacteria with decreasing temperature below 15°C corresponded with a loss of BSR performance across all three reactors. This study demonstrated the impact of low temperature on the physiological selection and ecological differentiation of SRB and SOB communities within the hybrid LFCR and its implications for real-world process performance.